Therapeutic Effects of Levocarnitine or Vitamin B Complex and E With Selenium on Glycerin-Treated Holstein Friesian Cows With Clinical Ketosis - Ha, Seungmin; Kang, Seogjin; Han, Manhye; Lee, Jihwan; Chung, Hakjae; Kim, Donghyeon; Park, Jinho (Frontiers in Veterinary Science, 2021)
Currently, ketosis has no fully satisfactory resolution in dairy cows. Here, we investigated the effect of levocarnitine or vitamin B complex and E with selenium on clinically ketotic cows (β-hydroxybutyrate ≥ 3.0 mmol/L and decreased milk yield), fed glycerin. In total, 18 cases of Holstein cows with clinical ketosis during the postpartum transition period were randomly assigned to three treatments (6 cases per group): (1) levocarnitine (C+G), (2) vVitamin B complex and E with sSelenium (VBES+G), and (3) levocarnitine and vitamin B complex and E with selenium (C+VBES+G). All groups were administered glycerin. Treatments were administered daily for four days. Blood sampling was performed on the onset day of ketosis (day 0), day 4, and day 6. β-Hydroxybutyrate (BHBA), milk yield (MY), and serum biochemical values were measured. Half of the animals in C+G failed to overcome clinical ketosis. VBES+G treatment ameliorated BHBA (p < 0.05), MY, and glucose on day 4. However, ketosis was exacerbated following the discontinuation of the treatment.afterward. C+VBES+G treatment improved BHBA, glucose (p < 0.05), and MY and reduced ketotic cases on days 4 and 6 with greater improvements compared to the others. In conclusion, combined treatment with levocarnitine, vitamin B complex and E with selenium, and glycerin may have the therapeutic effect on clinical ketosis.